1997
DOI: 10.1051/jp4:1997391
|View full text |Cite
|
Sign up to set email alerts
|

Shock Behaviour of 3D Carbon-Carbon Composite

Abstract: . The compressive response of a 3D carbon-carbon composite under shock wave was studied in a plateimpact configuration. Two directions of in~pact were achieved until a nominal value of longitudinal stress of 2.5 GPa. The measured wave profiles are consistent with previous results on 3D composites and confirm the behavim of such materials under impact. It is shown that the initial loading is decomposed in two waves. The first one is transmitted by the longil~rdinal fibres, the second one correspouds to the prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
18
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 3 publications
4
18
1
Order By: Relevance
“…1.0 GPa, followed by a much steeper rise to the final stress amplitude. This is qualitatively similar to the traces observed by Bordzilovsky et al [18] and Hereil et al [19] who proposed either an elastic precursor or a high velocity wave front transmitted along the fibres respectively.…”
Section: Figure 4 Near Heresupporting
confidence: 80%
See 4 more Smart Citations
“…1.0 GPa, followed by a much steeper rise to the final stress amplitude. This is qualitatively similar to the traces observed by Bordzilovsky et al [18] and Hereil et al [19] who proposed either an elastic precursor or a high velocity wave front transmitted along the fibres respectively.…”
Section: Figure 4 Near Heresupporting
confidence: 80%
“…This was interpreted as an elastic wave. Hereil et al [19] observed similar behaviour in a three dimensional carbon -carbon composite, with a low amplitude ramp preceding a much more quickly rising shock front. However, their interpretation suggested that this precursor was due to a high velocity wave transmitted along the fibres orientated in the shock axis, whilst the main shock was transmitted through the "matrix", in this case the fibres and binder orientated orthogonally, in agreement with previous studies [16,17].…”
mentioning
confidence: 53%
See 3 more Smart Citations